Role of pet animals (dogs, cats) for emerging and re-emerging zoonoses disease: Review - Abebe Garoma; Sagni Diba (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
A pet has been shared in the environment many times and also they are bringing major psychological well-being to society. However, dogs and cats were a carrier of microorganisms that are pathogens for human infection, like viral, bacterial, parasitic, and others. From those pathogens are the emerging or re-emerging viral zoonoses for a human being, such as rabies, cowpox, rotaviruses, and others. Bacterial infections include scratches, pasteurellosis, Staphylococcus aureus, Leptospira, and tuberculosis leading to severe cases for people because of the different factors which occur in pet animals. Similarly, parasitic infections including hydatidosis, and leishmaniasis, are also recalled as pet-related zoonotic diseases. Lack of Veterinary care, good personal hygiene and pet hygiene, and absence of health education are the factors such as a risk of zoonotic infection.